Click and release: bioorthogonal approaches to "on-demand" activation of prodrugs. (6th February 2019) - Ji, Xingyue; Pan, Zhixiang; Yu, Bingchen; De La Cruz, Ladie Kimberly; Zheng, Yueqin; Ke, Bowen; Wang, Binghe
Abstract : This review summarizes recent developments in using bioorthogonal chemistry in prodrug design for the delivery of traditional small molecule- and gasotransmitter-based therapeutics. Abstract : Prodrug approaches represent an excellent solution to certain pharmaceutical issues commonly encountered in the drug discovery and development process. Along this line, the chemistry needed for the bio-reversible derivatization of drug functional groups for on-demand release is critical. In recent years, "click and release" approaches have shown great promise in the design of prodrugs because of their bioorthogonality and controlled bond-cleavage, which help ensure prodrug stability during circulation and ready cleavage at the desired site of action. This review highlights recent developments of this research field and discusses issues yet to be addressed.